The Cambridge handbook of AI and consumer law comparative perspectives - DiMatteo, Larry A. 1957-; Poncibò, Cristina 1973-; Howells, Geraint G. (Cambridge law handbook, 2024)
"A first of its kind book with a breadth of coverage on the relationship between Artificial Intelligence and consumers from legal, social, and ethical perspectives. Expert"--